MENINGKATKAN MOTIVASI BELAJAR AL-QUR’AN DENGAN SISTEM MAPATO’ DI KELURAHAN BUAKANA - Fatmawati Hilal; Fitriani Kadir; Eri Sarmila (PPM LP2M UIN Alauddin Makassar, 2021)
Real Work Lecture (KKN) is a form of community service activity by students with a cross-scientific and sectoral approach at a certain time and area. The implementation of KKN activities usually lasts between one to two months and takes place in village-level areas. The Directorate General of Higher Education in Indonesia has requires every university to carry out KKN as an intracurricular activity that combines the tri dharma of higher education, namely: education, research, and community service. The approach method used in community service is social intervention, where social intervention is an effort to plan changes to individuals, groups, and communities with the principles of kinship and independence. The main purpose of social intervention is to improve social functions (individuals, groups, communities) which are the target of change, when a person's social functions function well, it is assumed that welfare conditions will be more easily achieved. The most important stage in the intervention is data collection, which is the stage where the social worker collects the information needed regarding the problem to be solved. This can help the community in implementing development in various fields, especially education, health, religion, and social affairs. This KKN student carried out activities at the Al-Muslimun Mosque, Buakana Village, Rappocini District, Makassar City. The residents of Bontolempangan Village generally welcome the arrival of students to bring about change through community empowerment in improving the quality of education, health, religion and social life.